PENDIDIKAN ANTIKORUPSI TERHADAP GENERASI ALPHA MENGGUNAKAN PENDEKATAN BELA NEGARA - Aji Lukman Ibrahim; Dian Khorenita Pratiwi; Suprima; Aditama Candra Kusuma; Ayu Diah Rahmani; Rindu Audrye (Politeknik Negeri Sriwijaya, 2022)
This community service uses the lecture, counseling, and discussion methods titled